An Improved 2-Aminoimidazole Based Anti-Biofilm Coating for Orthopedic Implants: Activity, Stability, and in vivo Biocompatibility - Coppola, Guglielmo Attilio; Onsea, Jolien; Moriarty, T. Fintan; Nehrbass, Dirk; Constant, Caroline; Zeiter, Stephan; Aktan, Merve Kübra; Braem, Annabel; Van der Eycken, Erik V.; Steenackers, Hans P.; Metsemakers, Willem-Jan (Frontiers in Microbiology, 2021)
Orthopedic device-related infections remain a serious challenge to treat. Central to these infections are bacterial biofilms that form on the orthopedic implant itself. These biofilms shield the bacteria from the host immune system and most common antibiotic drugs, which renders them essentially antibiotic-tolerant. There is an urgent clinical need for novel strategies to prevent these serious infections that do not involve conventional antibiotics. Recently, a novel antibiofilm coating for titanium surfaces was developed based on 5-(4-bromophenyl)-N-cyclopentyl-1-octyl-1H-imidazol-2-amine as an active biofilm inhibitor. In the current study we present an optimized coating protocol that allowed for a 5-fold higher load of this active compound, whilst shortening the manufacturing process. When applied to titanium discs, the newly optimized coating was resilient to the most common sterilization procedures and it induced a 1 log reduction in biofilm cells of a clinical Staphylococcus aureus isolate (JAR060131) in vitro, without affecting the planktonic phase. Moreover, the antibiofilm effect of the coating in combination with the antibiotic cefuroxime was higher than cefuroxime treatment alone. Furthermore, the coating was successfully applied to a human-scale fracture fixation device resulting in a loading that was comparable to the titanium disc model. Finally, an in vivo biocompatibility and healing study in a rabbit osteotomy model indicated that these coated implants did not negatively affect fracture healing or osteointegration. These findings put our technology one step closer to clinical trials, confirming its potential in fighting orthopedic infections without compromising healing.